Pengaruh Volatilitas Penjualan, Ukuran Perusahaan dan Arus Kas Operasional Terhadap Persistensi Laba - Putri, Ni Putu Cristina Ananda; Nilwan, Afrizal (Owner : Riset dan Jurnal Akuntansi, 2024)
Earnings persistence has a crucial role in reflecting the quality that refers to the earnings of a related company. This has a probability in the future while avoiding a number of risks related to liquidation. This study has a specific purpose in conducting tests on sales volatility, which is then related to company size as well as operating cash flow, which has an influence on earnings persistence, specifically referring to companies in the property and real estate sectors during the 2020–2022 period. The sample of this research includes 177 data points originating from 67 companies in the sector that are officially listed on the IDX. This research method involves a descriptive method involving a quantitative-based approach. The technique is to use purposive sampling. Then, data analysis is realized by multiple linear regression analysis methods utilizing software, namely SPSS for version 2018. The findings of this research explain the partial effect that leads to operational cash flow, which has a negative and significant effect on earnings persistence in companies engaged in the realm of property and real est ate. As for the sales volatility variable and company size, they do not have a significant influence on earnings persistence in the company.